2019
DOI: 10.1073/pnas.1910444117
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-wide observation of the phenomenon of life on the edge of solubility

Abstract: To function effectively proteins must avoid aberrant aggregation, and hence they are expected to be expressed at concentrations safely below their solubility limits. By analyzing proteome-wide mass spectrometry data of Caenorhabditis elegans, however, we show that the levels of about three-quarters of the nearly 4,000 proteins analyzed in adult animals are close to their intrinsic solubility limits, indeed exceeding them by about 10% on average. We next asked how aging and functional self-assembly influence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 72 publications
(99 reference statements)
9
127
0
Order By: Relevance
“…To rationalize these observations, it has recently been reported that a large fraction of the proteome is inherently metastable against aggregation within the cellular environment (Ciryam et al, 2013Yerbury et al, 2019). Proteins are metastable in their native states when their cellular concentrations exceed their intrinsic solubilities (Tartaglia et al, 2007;Vecchi et al, 2020). Indeed, proteins that coaggregate in plaques, tangles, and Lewy bodies have been found to be highly metastable against aggregation (Ciryam et al, 2013), and biochemical pathways associated with neurodegenerative diseases, including in particular oxidative phosphorylation, have been reported to be enriched in these proteins, hereafter referred to as metastable proteins, thus revealing a common feature for these otherwise very different neurodegenerative conditions (Ciryam et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To rationalize these observations, it has recently been reported that a large fraction of the proteome is inherently metastable against aggregation within the cellular environment (Ciryam et al, 2013Yerbury et al, 2019). Proteins are metastable in their native states when their cellular concentrations exceed their intrinsic solubilities (Tartaglia et al, 2007;Vecchi et al, 2020). Indeed, proteins that coaggregate in plaques, tangles, and Lewy bodies have been found to be highly metastable against aggregation (Ciryam et al, 2013), and biochemical pathways associated with neurodegenerative diseases, including in particular oxidative phosphorylation, have been reported to be enriched in these proteins, hereafter referred to as metastable proteins, thus revealing a common feature for these otherwise very different neurodegenerative conditions (Ciryam et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While at low protein concentrations, hydrogen bonds form intra-molecularly, leading to the formation of protein secondary structures, such as α-helices and β-sheets that are characteristic of the native states of proteins, at high concentrations, the formation of inter-molecular hydrogen bonds is favored, so that proteins tend to self-assemble into a highly ordered structures known as amyloid fibrils, which are stabilized by a network of hydrogen bonds [ 12 ]. The second observation is that the cellular concentrations of proteins are typically close to the critical values that define whether the most stable state is the native or the amyloid state [ 13 , 14 , 15 ]. This observation, which has been referred to as “life at the edge of solubility” [ 13 ], has an evolutionary origin.…”
Section: Protein Aggregation and Its Links With Neurodegenerative mentioning
confidence: 99%
“…As a result, proteins tend to be supersaturated in the cellular environment and they are, therefore, on the edge of aggregation [ 16 , 17 ]. Although it is perhaps surprising, we now know that proteins commonly aggregate under physiological conditions [ 15 ], and it is only the presence of a strong protein homeostasis system that prevents the progressive accumulation of large protein deposits [ 12 ]. Overall, the natural tendency of proteins to aggregate when they are supersaturated predisposes certain cell and tissues to protein aggregation upon stress or ageing [ 18 , 19 , 20 , 21 ].…”
Section: Protein Aggregation and Its Links With Neurodegenerative mentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining methods are trained with PON-Sol data [4] or not trained at all. Although many proteins are poorly soluble their solubility is biologically sufficient as many proteins have very low abundance in cells [1]. Data extracted by DeepSol developers from Structural Biology Knowledgebase indicated that 45.2 % out of 129.643 tested inherent and heterologously expressed proteins in E. coli were soluble [11].…”
Section: Solubility Predictionmentioning
confidence: 99%